Offspring performance is well buffered against stress experienced by ancestors. (1st July 2020) - Pei, Yifan; Forstmeier, Wolfgang; Kempenaers, Bart
Abstract: Evolution should render individuals resistant to stress and particularly to stress experienced by ancestors. However, many studies report negative effects of stress experienced by one generation on the performance of subsequent generations. To assess the strength of such transgenerational effects we propose a strategy aimed at overcoming the problem of type I errors when testing multiple proxies of stress in multiple ancestors against multiple offspring performance traits, and we apply it to a large observational dataset on captive zebra finches ( Taeniopygia guttata ). We combine clear one‐tailed hypotheses with steps of validation, meta‐analytic summary of mean effect sizes, and independent confirmatory testing. We find that drastic differences in early growth conditions (nestling body mass 8 days after hatching varied sevenfold between 1.7 and 12.4 g) had only moderate direct effects on adult morphology (95% confidence interval [CI]: r = 0.19–0.27) and small direct effects on adult fitness traits ( r = 0.02–0.12). In contrast, we found no indirect effects of parental or grandparental condition ( r = −0.017 to 0.002; meta‐analytic summary of 138 effect sizes), and mixed evidence for small benefits of matching environments between parents and offspring, as the latter was not robust to confirmatory testing in independent datasets. This study shows that evolution has led to a remarkable robustness of zebra finches against undernourishment. Our study suggests that transgenerational effects are absent in this species, because CIs exclude all biologically relevant effect sizes.